2022
DOI: 10.1126/science.abg2653
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase USP8 targets ESCRT-III to promote incomplete cell division

Abstract: In many vertebrate and invertebrate organisms, gametes develop within groups of interconnected cells called germline cysts formed by several rounds of incomplete divisions. We found that loss of the deubiquitinase USP8 gene in Drosophila can transform incomplete divisions of germline cells into complete divisions. Conversely, overexpression of USP8 in germline stem cells is sufficient for the reverse transformation from complete to incomplete cytokinesis. The ESCRT-III proteins CHMP2B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
0
17
2
1
Order By: Relevance
“…However, the fact that we observed neither cells interconnected as syncytia (i.e. more than 2 connected cells in a row) nor microtubule-bare ICs, both of which are features observed in IBs (Haglund et al, 2011; Mathieu et al, 2022), suggests that many of the ICs we observed differ from IBs previously described in gonad maturation (Haglund et al, 2011).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…However, the fact that we observed neither cells interconnected as syncytia (i.e. more than 2 connected cells in a row) nor microtubule-bare ICs, both of which are features observed in IBs (Haglund et al, 2011; Mathieu et al, 2022), suggests that many of the ICs we observed differ from IBs previously described in gonad maturation (Haglund et al, 2011).…”
Section: Discussioncontrasting
confidence: 91%
“…If the 30 ICs were in fact CBs, an explanation could be that cytokinesis in GCs takes longer than mitosis. Another may be that at least some GCs deliberately retain their CBs in order to keep cells attached in a manner similar to IBs, stable CBs that form as a result of incomplete cytokinesis in spermatogonial cells (Braun et al, 1989; Mathieu et al, 2022). IBs could serve as a scaffold to transport key proteins to control cell polarization (Zenker et al, 2017), or synchronize future divisions (Espinosa and Luo, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We first monitored the localization of Shrub. Because available anti-Shrub antibodies give no obvious membrane associated signal following chemical fixation (data not shown; (Pannen et al, 2020)), we made use of a GFP tagged version of Shrub engineered by CRISPR/Cas9 (ShrubGFP, (Mathieu et al, 2022)). We then live-imaged MyoRFP and ShrubGFP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stable cytokinetic cellular bonds are found in germlines (i.e. sexual gamete cells) of metazoans ranging from insects to hu-mans [15]. During gametogenesis, gametes divide and form cluster of cells interconnected in syncytia (a large structure formed by the joining several cells).…”
Section: La Version Française De L'article Est Disponible à La Suite ...mentioning
confidence: 99%
“…Cette cytokinèse incomplète se produit dans les organismes multicellulaires clonaux tels que les animaux, les plantes terrestres, les champignons et les algues, et donne lieu à la création de ponts intercellulaires stables qui seront d'une importance vitale pour les cellules tout au long de leur vie. On trouve des liens cellulaires cytocinétiques stables dans les lignées germinales (c'est-à-dire les cellules des gamètes sexuels) des métazoaires, des insectes aux humains [15]. Pendant la gamétogenèse, les gamètes se divisent et forment des amas de cellules interconnectées en syncytia (une grande structure formée par la réunion de plusieurs cellules).…”
Section: Version Françaiseunclassified